Fermentação metanogênica mesofílica de melaço e termofílica de vinhaça em reatores UASB - Faria, Alexandre Aníbal Antunez [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study evaluate the performance of an upflow anaerobic sludge blanket (UASB) in the mesophilic temperature range using molasses sugar cane diluted as substrate. The UASB reactor operated at a hydraulic retention time (HRT) of 24 hours and organic load rate (OLR) averages of up to 15 g total COD (L d)-1 and total recirculation of the effluent of the UASB reactor was used to dilute the molasses. The inoculum used was from a thermophilic UASB reactor treating vinasse. Volumetric and specific yields of methane from methane production to 0.97 N LCH4 (L d) -1 and 0.194 L CH4 (g total COD removed) -1, respectively, which indicated the adaptation of microorganisms using molasses were observed sugar-provided supplemental alkalinity, nitrogen and phosphorus is performed. Remove values of chemical oxygen demand of 64 at 72%, with base addition molasses. Also evaluated the performance of two UASB reactors in series in the thermophilic temperature range using the diluted vinasse as substrate. The reactors were operated at HRT of 16 and 7.5 h, respectively, and average OLR of 20 and 35 g total COD (L d) -1, respectively. The inoculum used was derived from mesophilic UASB reactor treating molasses. Specific and volumetric yield of methane production LCH4 to 0.46 N (L d) -1 and 0.16 L CH4 (g totalCOD removed) -1, respectively, which indicated the adaptation of the microorganisms were observed

Neste trabalho avaliou-se o desempenho de um reator UASB na faixa de temperatura mesofílica utilizando o melaço de cana-de-açúcar diluído como substrato. O reator UASB foi operado TDH de 24 h com COV médias de até 15 g DQOtotal (L d)-1 e foi utilizada a recirculação total do efluente do reator UASB, para diluir o melaço. O inoculo utilizado era proveniente de um reator UASB termofílico tratando vinhaça. Foram observadas produção volumétrica e produção específica de metano de até 0,97 N LCH4 (L d)-1 e de 0,194 L CH4 (g DQOtotal removida)-1, respectivamente, o que indicou a adaptação da microbiota utilizando melaço de cana-de-açúcar, desde que seja realizada a suplementação de alcalinidade, nitrogênio e fósforo. Foram observados valores médios de remoção de demanda química de oxigênio, de 64 a 72%, com base na DQOtotal do melaço adicionado.Também avaliou-se o desempenho de dois reatores UASB em série na faixa de temperatura termofílica utilizando a vinhaça diluída como substrato. Os reatores foram operados com TDH de 16 e 7,5 h, respectivamente e COV média de 20 e 35 g DQOtotal (L d)-1 , respectivamente. O inoculo utilizado era proveniente do reator UASB mesofilico tratando melaço. Foram observadas produção volumétrica e produção específica de metano de até 0,46 N LCH4 (L d)-1 e de 0,16 L CH4 (g DQOtotal removida)-1, respectivamente ...
Keywords: Biogas; Metano; Reatores UASB; Melaço; Vinhaça; Fermentação; Methane